The Determination of Willingness to Pay for Electrical Vehicles: A Literature Review - Tuladhar, Unnati; Yuangyai , Nuttaya; Pengsakul , Theerakamol; Gyawali , Saroj (International Journal of Energy Economics and Policy, 2023)
With growing concerns about climate change and an unreliable fuel market, the world is shifting toward an electric-based transportation system, which requires a country to overhaul major infrastructures, establish highly funded research, change government regulations, and adapt available resources in order to transition from a gasoline-based transportation system to an electric one. The study is focused on consumers’ determination of willingness to pay for electrical vehicles. By examining consumers' intentions to buy or not buy electric vehicles, researchers are attempting to determine what factors are motivating them to do so which may be range factor, demographic factors, marketing, charging station, government policy. The review studies show the various factors for determination of willingness to pay for electric vehicle.